Glutamate Pays Its Own Way in Astrocytes - McKenna, Mary C. (Frontiers in Endocrinology, 2013)
In vitro and in vivo studies have shown that glutamate can be oxidized for energy by brain astrocytes. The ability to harvest the energy from glutamate provides astrocytes with a mechanism to offset the high ATP cost of the uptake of glutamate from the synaptic cleft. This brief review focuses on oxidative metabolism of glutamate by astrocytes, the specific pathways involved in the complete oxidation of glutamate and the energy provided by each reaction.